Model Iklan Layanan Masyarakat Berbasis Animasi - Anung Rachman (Ornamen, 2008)
Advertising is a media that usually used for direct persuasif communication by company to consumer. Advertisement device be created to make human become easy for understand to the advertisement message. Information technology as the helper device in understanding process. Multimedia animation as an information technology part able to support in understanding. In this paper, I will show that multimedia animation can give any pleasure and helping understand process in intend.Key word: Understanding, advertisement, Multimedia animation